A key cytochrome P450 hydroxylase in pradimicin biosynthesis - Napan, Kandy L. (2011)
Pradimicins A-C (1–3) are a group of antifungal and antiviral polyketides from Actinomadura hibisca. The sugar moieties in pradimicins are required for their biological activities. Consequently, the 5-OH that is used for glycosylation plays a critical role in pradimicin biosynthesis. A cytochrome P450 monooxygenase gene, pdmJ, was amplified from the genomic DNA of A. hibisca and expressed in Escherichia coli BL21(DE3). PdmJ introduced a hydroxyl group to G-2A (4), a key pradimicin biosynthetic intermediate, at C-5 to form JX134 (5). A D-Ala-containing pradimicin analog, JX137a (6) was tested as an alternative substrate, but no product was detected by LC-MS, indicating that PdmJ has strict substrate specificity. Kinetic studies revealed a typical substrate inhibition of PdmJ activity. The optimal substrate concentration for the highest velocity is 115 μM under the test conditions. Moreover, the conversion rate of 4 to 5 was reduced by the presence of 6, likely due to competitive inhibition. Coexpression of PdmJ and a glucose 1-dehydrogenase in E. coli BL21(DE3) provides an efficient method to produce the important intermediate 5 from 4.